Cell Therapy to Induce Allograft Tolerance: Time to Switch to Plan B? - Sicard, Antoine; Koenig, Alice; Morelon, Emmanuel; Defrance, Thierry; Thaunat, Olivier (Frontiers in Immunology, 2015)
Organ transplantation is widely acknowledged as the best option for end stage failure of vital organs. Long-term graft survival is however limited by graft rejection, a destructive process resulting from the response of recipient’s immune system against donor-specific alloantigens. Prevention of rejection currently relies exclusively on immunosuppressive drugs that lack antigen specificity and therefore increase the risk for infections and cancers. Induction of donor-specific tolerance would provide indefinite graft survival without morbidity and therefore represents the Grail of transplant immunologists. Progresses in the comprehension of immunoregulatory mechanisms over the last decades have paved the way for cell therapies to induce allograft tolerance. The first part of the present article reviews the promising results obtained in experimental models with adoptive transfer of ex vivo-expanded regulatory CD4+ T cells (CD4+ Tregs) and discuss which source and specificity should be preferred for transferred CD4+ Tregs. Interestingly, B cells have recently emerged as potent regulatory cells, able to establish a privileged crosstalk with CD4+ T cells. The second part of the present article reviews the evidences demonstrating the crucial role of regulatory B cells in transplantation tolerance. We propose the possibility to harness B cell regulatory functions to improve cell-based therapies aiming at inducing allograft tolerance.